Patriarchy Sanctioned Under Religious Fanaticism The Nervous Condition Of Muslim And Christian Womanhood - Wahiba Nouioua (The Journal of Studies in Language, Culture and Society)
This article intends to unravel the myth of eternal feminine in Muslim and Christian societies, by exploring the gender asymmetry inscribed within as being traditionally and religiously reinforced by the patriarchal social order. Particularly, this asymmetry is generally maintained by unscrupulous representatives of religion, who seek to incarnate an unquestionable godly power that is oppressive to the female sex. Gender bias, in this regard, becomes justified in the name of God, or through a repressive discourse of righteousness which is male-prescribed and male-maintained, but claimed to be divinely ordained. With the patriarchalisation of religious tenets, women become further incapacitated to improve their lot and thus stifle the patriarchal energy seeking to relegate them to the auxiliary status. Using Nawal El Saadawi‟s God Dies by The Nile and Chimamanda Ngozi Adichie‟s Purple Hibiscus, the article tries to uncover the patriarchal distortions of Muslim and Christian cultures where misogynistic reading of religion is used against battered and sexually exploited women. The concern of this article is to depict, through the stories of these women, how the instrumentalization of religion by the patriarchal order can dangerously breed a chaotic culture which deliberately embraces a limited view regarding any female autonomous development. The paper shows through the protagonists‟ dissident acts that to break free from the phallocratic mentality, women need to dogmatically and indignantly dethrone those God abstractions inflicted on their consciousness. A participation in de-patriarchizing oppressive God images will empower these subaltern women to cease playing the game of sex roles, imposed on them by the patriarchal social order.